Kumori: Teaching Media for Interactive Japanese Language Learning - Sutiyarti, Ulfah; Emaliana, Ive; Putra, Edy (JAPANEDU: Jurnal Pendidikan dan Pengajaran Bahasa Jepang, 2019)
This paper centers around the ideas of developing students' media literacy through integrating Japanese language learning and multimedia form. This media is utilized to facilitate Japanese irregular verbs (Doushi) learning on the basis of morphological changes. One of Japanese verb forms which is employed frequently are words which have suffix -te, for they are use ask, order and allow interlocutors to do something (-te kudasai); to show present activities (-te imasu), to give permission (-temo ii desu); and to show prohibitions (-tewa ikemasen). Preliminary study elucidated that students found these Doushiare problematic and complex; thus, additional learning media to learn autonomously is inevitable for students to practice outside the classroom tasks. Researchers attempt to achieve this by developing appropriate teaching media by using Macromedia Flas8 software based on ADDIE model research and design steps, including Analysis, Design, Development and Implementation, Evaluation. The media is called Kumori, which provides interactive and meaningful media for student self-directed learning. The findings shows that Kumorias the instructional media in learning Japanese vocabulary which follows steps of the ADDIE model in order to produce an effective and efficient instructional tool for language learning, can give positive impact to students’ academic achievement. Therefore, adopting an appropriate instructional model must because it is a systematic process in developing proper instructional materials for an effective education and training program. Further, Kumorialso expected to able to contribute and implicated in Japanese language teaching and learning.